Identifikasi Proses Pergerakan Massa Tanah Di Desa Rumengkor Kecamatan Tombulu - Ginavie A. Pakasi; Lientje Th. Karamoy; Zetly E. Tamod; Maria Montolalu (Universitas Sam Ratulangi, 2015)
ABSTRACT The study aims to identify the occurrence of mass movement in the village Rumengkor and calculate the volume of soil that experienced mass movement in the village Rumengkor. The research was carried for three months from June to August 2014. Research using survey method with the method of design through several stages which includes the identification of mass movement through the inventory and analysis (taking into account the secondary data and primary data darihasil laboratory analysis and the results of field measurements), then calculate the volume of soil that is moved through the tread design drawings. The identification results of the mass movement of land in the village of Rumengkor shows there has been a process of disengagement from the connective power (cohesion) soil / rock and roots are weak so that the granules soil / rock can be released from his bonds and then a process of transporting / moving to the bottom of the slope by dragging Other grains around it to form a larger mass and settles on the bottom of the slope (98m). Weak holding capacity soil / rock can be caused by a rock that is not compact, the physical properties of the dominant clay soil texture, water break-out properties (permeability) moderate to fast which is supported by high rainfall, the ground cracks, the scarcity of ground cover plants and Volume space land of productive land are lost as a result of mass movement in the village of Rumengkor calculated from the movement of the tread design perspective 7199.25 m3. Â Keywords : Land Mass, Cohesion and Permeability